Letter to the Editor concerning “Impact of preoperative mental health disorders on postoperative outcomes in patients with adolescent idiopathic scoliosis undergoing surgery” by Vallee EK, et al. (Spine Deformity [2026]: doi:10.1007/s43390-026–01288-z) - Kishankumar Mahida; Snehal Rajendra Jagtap (Spine Deformity, 2026)
PURPOSE: Social exclusion encompasses multiple domains, material, digital, relational, political, and structural. These may have different impacts on an individual's mental health. We evaluated associations between domains of social exclusion and mental health problems in a sample of English adults. METHODS: Using data from Understanding Society, we analysed social exclusion exposures and mental health outcomes at Wave 11 (2019-21) among 34,403 adults. We generated standardised domain scores and an overall social exclusion measure using principal component analysis. Mental health was assessed using the General Health Questionnaire (GHQ-12) continuous symptom scores (range 0-36). We used survey-weighted linear regression models adjusted for age, sex, and ethnicity. RESULTS: Each standard deviation increase in overall social exclusion was associated with 1.28-point increase in GHQ-12 symptoms (95% CI: 1.11,1.44). Domain-specific analyses showed the strongest associations for material exclusion ([Formula: see text]=1.34, 95% CI: 1.20,1.47) and relational exclusion ([Formula: see text]=1.37, 95% CI:1.09,1.65). Digital, political, and structural exclusion showed smaller positive associations ([Formula: see text]=0.15 to 0.37). Associations did not differ by sex and remained robust when examining mental health caseness as a binary outcome. CONCLUSION: Social exclusion was associated with worse mental health, with strongest effects for relational and material domains. Policies targeting these domains may have the largest impact on population mental health.